Effects of social media and smartphone use on body esteem in female adolescents: Testing a cognitive and affective model - YANG, Hwajin (Institutional Knowledge at Singapore Management University, 2020)
We examined the predictive relations of social media and smartphone use to body esteem in female adolescents and the mechanism that underlies these relations. As a result of frequent social media and smartphone use, adolescents are continually exposed to appearance-related media content. This likely reinforces a thin ideal and fosters appearance-based comparison and increases fear of external evaluation. Hence, we investigated a cognitive-affective framework in which the associations of social media and smartphone use with body esteem are serially mediated by cognitive internalization of an ideal body image, appearance comparisons, and social appearance anxiety. By testing female adolescents (N = 100) aged 13 to 18, we found that excessive social media use leads to unhealthy body esteem via intensified cognitive internalization, which aggravates appearance comparisons and anxiety regarding negative appearance evaluation. Further, we found that screen time for specific smartphone activities also harmed body esteem, independent of social media use. However, overall smartphone screen time did not affect body esteem when social media use was taken into consideration. Our findings underscore the multifactor mechanism that elucidates the negative impacts of social media and smartphone activities on body esteem in female adolescents, who are developmentally susceptible to poor body esteem.